Oxide state evaluation of magnesium and calcium in thin metallic film using Auger electron spectroscopy depth profiles. (26th October 2015) - Mandrino, D.; Nolan, D.
Abstract : Topmost layer of a submicrometre Zn–Al corrosion protection metallic coating containing also Mg and Ca as minor constituents was depth profiled using Auger electron spectroscopy. Oxidation state dependent kinetic energy shifts of the Mg KLL and Ca LMM peaks were used to evaluate the oxide state of the respective minor elements along the profile. An attempt was also made to obtain a quantitative estimate of the oxidised versus total ratio for both elements at given depth. Linear least squares fitting was used to fit the peak shapes of the measured Mg KLL and Ca LMM peaks by linear combinations of the peak shapes corresponding to the oxide and metallic states. Results obtained by the two techniques were compared and found consistent.